2008
DOI: 10.1007/s10641-008-9331-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paternity is prevalent in Pacific ocean perch (Sebastes alutus) off the Oregon coast, and is correlated with female size and age

Abstract: The need to rebuild Pacific ocean perch, Sebastes alutus, populations on the west coast of the United States has precipitated a need to better understand the life history characteristics of this rockfish species. One such characteristic is mating behavior, which has the potential to influence the amount of genetic diversity in a population. We documented and examined the frequency of multiple mating in Pacific ocean perch collected off the Oregon coast using five microsatellite loci. We found that 47 of 66 (71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Even though their study did not show a simple relationship between female body size and rates of multiple paternity in the sailfin molly, other studies have shown a tendency for broods of larger females to have more sires. For example, the rate of multiple paternity is positively correlated with female body size in bonnethead sharks (Chapman et al ., 2004), least killifish (Soucy & Travis, 2003), and Pacific ocean perch (Van Doornik et al ., 2008). Nevertheless, this pattern is not ubiquitous because other studies have failed to find a significant relationship (Zane et al ., 1999; Portnoy et al ., 2007; Neff, Pitcher & Ramnarine, 2008; Daly‐Engel et al ., 2010), indicating that many factors, which probably differ in relative importance among species, conspire to shape female mating patterns.…”
Section: Population‐level Variation In Multiple Parentage Within Speciesmentioning
confidence: 99%
“…Even though their study did not show a simple relationship between female body size and rates of multiple paternity in the sailfin molly, other studies have shown a tendency for broods of larger females to have more sires. For example, the rate of multiple paternity is positively correlated with female body size in bonnethead sharks (Chapman et al ., 2004), least killifish (Soucy & Travis, 2003), and Pacific ocean perch (Van Doornik et al ., 2008). Nevertheless, this pattern is not ubiquitous because other studies have failed to find a significant relationship (Zane et al ., 1999; Portnoy et al ., 2007; Neff, Pitcher & Ramnarine, 2008; Daly‐Engel et al ., 2010), indicating that many factors, which probably differ in relative importance among species, conspire to shape female mating patterns.…”
Section: Population‐level Variation In Multiple Parentage Within Speciesmentioning
confidence: 99%
“…No evidence of multiple paternity was found in broods from quillback rockfish. Multiple paternity has been described in 13 of 21 rockfish species examined to date (Yoshida et al 2001, Hyde et al 2008, Sogard et al 2008, Van Doornik et al 2008, Blanco Gonzalez et al 2009, and seems to be common in the genus. Considering the close relationship of copper and quillback rockfishes (Hyde & Vetter 2007), the absence of evidence of multiple paternity in quillback rockfish in the present study may be a consequence of low sample size, rather than evidence that it does not occur.…”
Section: Parentage Analysismentioning
confidence: 99%
“…Multiple paternity may be a bet-hedging strategy for rockfishes when a female's knowledge of mate selection criteria is imperfect (Yasui 2001). Such a strategy may improve the genetic diversity of offspring from a single female, thereby improving the odds that some fraction of her larvae encounter favorable environmental conditions and survive (Cushing 1990, Hyde et al 2008, Van Doornik et al 2008. Another potential benefit of multiple mating for individual females is the potential reduction in the probability of incomplete fertilization of eggs in a brood (Gunderson 1977, Sogard et al 2008.…”
Section: Parentage Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In situ observations convey that the most prominent male secondary sex trait is a transient, behavioral visual signal: courtship displays, either in the water column, or on territories (Helvey, ; Shinomiya & Ezaki, ). We posit that if multiple paternity is documented in a Sebastes species (Van Doornik, Parker, Millard, Berntson, & Moran, ; Hyde et al., ; Sogard et al., ), with schooling, nonterritorial behavior as adults, a likely genetic mating system would be a form of polygamy, as monogamy and polygyny are disqualified. Polyandry is also possible, but Sebastes species do not show sex‐role reversal characteristics in behavior or morphology (reviewed in Gwynne, ): females do not appear to compete for males (Helvey, ; Shinomiya & Ezaki, ), and no elaborated secondary sex traits are evident among females.…”
Section: Introductionmentioning
confidence: 99%